Our current understanding of metastasis and the potential for predicting the course of head and neck squamous cell carcinoma (Ukrainian Journal of Ophthalmology, 2025)
This review presents recent studies on the mechanisms of malignant neoplasm metastases, particularly, in head and neck squamous cell carcinoma (HNSCC). The involvement of circulating tumor cells (CTC) and cancer stem cells (CSC), and the role of epithelial-to-mesenchymal transition (EMT) and the reverse process, mesenchymal-to-epithelial transition (MET), in the establishment of metastases were noted. The major features of the EMT program are loss of E-cadherin-dependent intercellular adhesion of epithelial cells and increase in tumor cell motility and capacity for migration to and invasion of adjacent tissues and remote organs. Identifying the humoral and cell factors of epithelial cell  microenvironment which induce and regulate the capacity of these cells for malignant transformation is important not only for understanding the mechanisms of oncogenesis, but also for considering whether it is possible to use them as predictive markers or therapeutic targets, which is important for clinical practice.The review provides data on the role of CTC in the course of HNSCC. It has been demonstrated that the presence of CTCs in patient blood correlated with a higher clinical stage of the disease, thereby evidencing the significant prognostic value of CTC blood levels in head and neck cancer patients and that the presence of CTCs could be used as a monitoring tool for tumor status of head and neck cancer, especially for the early detection of the tumor recurrence and progression, advanced disease and metastases, and assistance in therapeutic effect assessment.A current approach to identifying the character of and predicting the clinical course of malignant neoplasms is based on the use of the lymph node ratio (LNR) defined as the number of positive lymph nodes divided by the total number of lymph nodes excised. Numerous studies demonstrated that the LNR has a predictive value in head and neck squamous cell carcinoma, may be used as an additional prognostic parameter in combination with the revised TNM classification in HNSCC to predict the course of disease, select adjuvant therapy and control therapy efficacy.
Keywords: head and neck squamous cell carcinoma; metastasis; circulating tumor cells; cancer stem cells; lymph node ratio (LNR)